Lipid desaturation-associated endoplasmic reticulum stress regulates MYCN gene expression in hepatocellular carcinoma cells - Qin, Xian-Yang (Cell Death Dis, 2020)
Hepatocellular carcinoma (HCC) is the second leading cause of cancer-related deaths worldwide due to its high rate of recurrence, in part because of cancer stem cell (CSC)-dependent “field cancerization”. Recently, we identified that the oncogene v-myc avian myelocytomatosis viral oncogene neuroblastoma derived homolog (MYCN) marked CSC-like subpopulations in heterogeneous HCC and served as a therapeutic target and prognostic marker for HCC. In this study, we explored the molecular basis of upregulated MYCN gene expression in HCC cells. Liquid chromatograph time-of-flight mass spectrometry-based metabolome analysis demonstrated that the content of unsaturated fatty acids was increased in MYCN high expression (MYCN(high)) CSC-like HCC cells. Inhibition of lipid desaturation using either the chemical inhibitor or siRNA/shRNA against stearoyl-CoA desaturase-1 (SCD1) suppressed cell proliferation as well as MYCN gene expression in MYCN(high) HCC cells, grown as both monolayer and spheres. Further mechanistic study using RNA-seq based transcriptome analysis revealed that endoplasmic reticulum (ER) stress related signaling networks such as endocannabinoid cancer inhibition pathway were under the control of SCD1 in MYCN(high) HCC cells. Furthermore, the expression of ER stress-inducible transcription suppressor cyclic AMP-dependent transcription factor (ATF3) was downregulated in MYCN(high) CSC-like HCC cells and CSC-rich spheroids, which was upregulated by inhibition of lipid desaturation or treatment with acyclic retinoid (ACR). Lipid profiling using NMR spectroscopy revealed that the ACR dramatically reduced the content of unsaturated fatty acids in HCC cells. The chemical inducer of ER stress inhibited MYCN gene expression, while the chemical inhibitor of ER stress or knockdown of ATF3 gene expression partially rescued the suppression of MYCN gene expression by ACR in MYCN(high) HCC cells. These data suggested that lipid desaturation-mediated ER stress signaling regulates MYCN gene expression in HCC cells and serves as a promising therapeutic target for the treatment and prevention of HCC.